Role of nursing professionals in identifying prescription errors (Research, Society and Development, 2022)
The objective of this study focuses on evaluating the role of nursing professionals in identifying the most common errors in medication prescriptions. This research was based on an integrative literature review, with a descriptive approach. Carried out through a survey of data in the scientific bases: SCIELO and BDENF. Upon analysis of the studies selected for the sample, all prescriptions must follow the guidelines relating to the user containing their personal information, address, route of administration, indicated medication, dose, quantity and its appropriate dosage. However, in the reality of public services, they are far from following the norms established as a requirement, which is unacceptable for the quality of service and patient safety. In this circumstance, among the most common predisposing factors for these prescription errors to occur are the lack of patient or professional information, where prescriptions may be incomplete or in illegible letters. Thus, this study highlighted the importance of incorporating health education, as well as the need to expand health education and promotion actions for good drug prescription practices. The nursing professional has an essential role in this process, especially with regard to informative adherence.